Restoration in primary molars placed by undergraduate dental students: reasons for failures - Harun, Nor Asilah; Yaacob, Munirah; Abdul `Alim, Mohamad Shafiq Aizuddin; Ghazali, Saifullah; Nik Khairuzaman, Nik Khairul Azmi (2021)
Dental caries is one of the most common chronic childhood diseases and highly prevalent in the world. The commonest treatment procedure for dental caries is a dental restoration which aims to retain the tooth. The survival of restoration depends on the factors associated with restorative materials, patients or operators. Thus, this study aimed to determine the reasons for the failure of restoration in posterior primary teeth performed by undergraduate dental students. A total number of 32 patients aged from 5 to 12 years old were included in this study. Overall, 115 primary molar restorations were assessed clinically using the modified United States Public Health Service Ryge criteria. The O’Leary plaque score was used to evaluate the oral hygiene status of all patients. Then, the data was analysed using the Kaplan-Meier survival curves with log-rank test and Cox regression analysis. 43 (37.4 %) restorations failed with 62.1 % for glass ionomer cement and 36.4 % for composite restorations. Marginal adaptation (62.8 %) is the commonest cause of failure. 76.7% of failure restoration was in patients with poor oral hygiene, and it showed a significant difference compared to patients with moderate and good oral hygiene (p = 0.014). Thus, it was concluded that the type of restorative material and oral hygiene status contributed to the failure of restoration placed in primary molar restorations with failure restoration may occur 2.6 times more in poor oral hygiene patients.